Monoclonal antibody therapy of diffuse cutaneous scleroderma with CAMPATH-1H. - Isaacs, J; Hazleman, B; Chakravarty, K; Grant, J; Hale, G; Waldmann, H (1996)
A worker in a polyvinyl chloride factory with rapidly progressive diffuse cutaneous scleroderma was treated with the humanized monoclonal antibody (Mab) CAMPATH-1H. Treatment was followed by rapid and substantial improvement in skin score, which was maintained during followup without additional therapy. The mode of action of CAMPATH-1H and its relationship to clinical improvement are discussed.